The Fruitghurt Formulations are Combination of Red Guava and Pineapple Juice by using the Encapsulation Method, as an Alternative Source of Vitamin C - Dewi Restuana Sihombing; Connie Daniela (Talenta Publisher, 2022)
Fruitghurt is a product of fermented fruit juice using Lactobacillus bulgaricus and Streptococcus thermophillus bacteria. This research was conducted of developing fruitghurt products that contain vitamin C with a combination of red guava and pineapple juice. The research method was carried out using a factorial completely randomized design method which consisted of two factors. Factor I: combination of red guava and pineapple juice: JN1=120%:80%; JN2=130%:70%, JN3=140%:60%, JN4=150%:50%. Factor II: drying time L1=1 hour, L2=2 hours, L3=3 hours, L4=4 hours. The results showed that the concentration of red guava and pineapple juice had a very significant effect (p<0.01) on vitamin C levels, total dissolved solids, total acids, water content, total LAB, antioxidant activity, organoleptic. The interaction between the concentration of red guava and pineapple juice and the drying time had a very significant (p<0.01) effect on total lactic acid bacteria, antioxidant activity, vitamin C and total dissolved solids. The best fruitghurt quality was obtained in the JN4L1 treatment combination with a vitamin C 4.92 mg/100g, total dissolved solids 8.85Â°Brix, total acid 1.50%, moisture content 4.98% and total lactic acid bacteria 12.95 log CFU/ml. Fruitghurt a formulation of red guava and pineapple juice is recommended as an alternative source of vitamin C.